2014
DOI: 10.1038/cdd.2014.121
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase TRIM32 negatively regulates tumor suppressor p53 to promote tumorigenesis

Abstract: Tumor suppressor p53 has a key role in maintaining genomic stability and preventing tumorigenesis through its regulation of cellular stress responses, including apoptosis, cell cycle arrest and senescence. To ensure its proper levels and functions in cells, p53 is tightly regulated mainly through post-translational modifications, such as ubiquitination. Here, we identified E3 ubiquitin ligase TRIM32 as a novel p53 target gene and negative regulator to regulate p53-mediated stress responses. In response to stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 54 publications
7
114
1
Order By: Relevance
“…Horn et al (13) investigated the association between TRIM32 expression levels and apoptosis signaling pathways and demonstrated that TRIM32 may be involved in cellular transformation and skin carcinogenesis via promoting the survival of cells over the induction of apoptosis (13). Liu et al (15) demonstrated that TRIM32 promotes p53 degradation via ubiquitination and that TRIM32 negatively regulates p53-mediated apoptosis, cell cycle arrest and senescence. Taken together, these results suggest that TRIM32 may negatively regulate cell proliferation and promote anti-apoptotic signaling pathways in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horn et al (13) investigated the association between TRIM32 expression levels and apoptosis signaling pathways and demonstrated that TRIM32 may be involved in cellular transformation and skin carcinogenesis via promoting the survival of cells over the induction of apoptosis (13). Liu et al (15) demonstrated that TRIM32 promotes p53 degradation via ubiquitination and that TRIM32 negatively regulates p53-mediated apoptosis, cell cycle arrest and senescence. Taken together, these results suggest that TRIM32 may negatively regulate cell proliferation and promote anti-apoptotic signaling pathways in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Human TRIM32 gene mutations have been detected in two genetic disorders, limb-girdle muscular dystrophy type 2H (11) and Bardet-Biedl syndrome (12). The overexpression of TRIM32 has been demonstrated in numerous types of human cancer, including lung and colorectal cancer and skin squamous cell, head and neck squamous cell and hepatocellular carcinoma (13)(14)(15). However, the expression levels of TRIM32 in gastric cancer remain to be established.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that this integrin may be integrated in the growing list of molecular determinants of the p53 tumorsuppressor activity. [61][62][63] Response to chemotherapy may be hindered by p53-mediated cell cycle arrest or senescence. 64,65 As shown here, functional inhibition of the α5β1 integrin may represent a new way to sensitize glioma cells to the p53-dependent proapoptotic effect of Nutlin-3a.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRIM8, TRIM13, TRIM19, TRIM21 and TRIM25 also affect p53 stability (Bernardi et al, 2004;Joo et al, 2011;Caratozzolo et al, 2012;Reddy et al, 2014;Zhang et al, 2015). TRIM28, TRIM29 and TRIM32 antagonize p53 function (Wang et al, 2005;Yuan et al, 2010;Liu et al, 2014). In turn, TRIMs and p53 affect each other transcriptionally.…”
Section: Role Of Trim-directed Precision Autophagy In Diseasementioning
confidence: 99%